HSF1 Attenuates LPS-Induced Acute Lung Injury in Mice by Suppressing Macrophage Infiltration. (18th December 2020) - Li, Tao; Xiao, Gui; Tan, Sipin; Shi, Xueyan; Yin, Leijing; Tan, Chuyi; Gu, Jia; Liu, Yanjuan; Deng, Huafei; Liu, Ke; Liu, Meidong; Zhang, Huali; et al.
Abstract : Heat shock factor 1 (HSF1) is a transcription factor involved in the heat shock response and other biological processes. We have unveiled here an important role of HSF1 in acute lung injury (ALI). HSF1 knockout mice were used as a model of lipopolysaccharide- (LPS-) induced ALI. Lung damage was aggravated, and macrophage infiltration increased significantly in the bronchoalveolar lavage fluid (BALF) and lung tissue of HSF -/- mice compared with the damage observed in HSF1 +/+ mice. Upon LPS stimulation, HSF -/- mice showed higher levels of monocyte chemoattractant protein-1 (MCP-1) in the serum, BALF, and lung tissue and increased the expression of MCP-1 and chemokine (C-C motif) receptor 2 (CCR2) on the surface of macrophages compared with those in HSF1 +/+ . Electrophoretic mobility shift assays (EMSA) and dual luciferase reporter assays revealed that HSF1 could directly bind to heat shock elements (HSE) in the promoter regions of MCP-1 and its receptor CCR2, thereby inhibiting the expression of both genes. We concluded that HSF1 attenuated LPS-induced ALI in mice by directly suppressing the transcription of MCP-1/CCR2, which in turn reduced macrophage infiltration.